Marketing Strategy of Pasarwajo Special Gule as Processed Cabium in the New Normal Period - Haerunianti Haerunianti; Hesti Lestari Ayu (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2023)
This study aims to formulate a marketing strategy that can be applied by the Pasarwajo typical gule snack products industry during the new normal period. This research is a case study design of Gule Wa Muri Household Industry located in Takimpo Village, Pasarwajo District, Buton Regency, Southeast Sulawesi, Indonesia. Data collection was carried out through observations, interviews and documentation studies. Data was analyzed descriptively and strategy formulation used SWOT and QSPM analysis. The results showed that the strength factor in the Gule Wa Muri house industry is greater than the weakness factor, and the opportunity factor is greater than the threat factor. The IE matrix shows that Gule Wa Muri's domestic industry is in cell V, indicating that this company is in a position of growth stability. The analysis results on the Cartesian SWOT Diagram show the position of the company in Quadrant I, which means that Home industries tend to be profitable, and various alternative strategies can be created to take advantage of the strengths and take advantage existing opportunities. The strategy suggested on the basis of the results of this analysis is to open marketing channels using information systems, to increase the purchasing power of consumers by providing quality products and affordable prices, and to expand businesses by recruiting workers and increasing business capital through the government's business capital assistance program.